THE INTERPRETATION OF OGAHI AS A LOVER IN NOVELS AND DRAMAS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article analyzes the portrayal of Muhammad Reza Erniyozbek's son Ogahi as a lover in the works of art. The historical novel " Hare tracks or Ogahiy " and the historical drama "Ogahiy" based on historical fact and artistic texture are compared and analyzed.